Analyse de la liaison dans le discours non spontané des apprenants hellénophones chypriotes de niveau intermédiaire/avancé - Valetopoulos, Freiderikos (My University, 2015)
The aim of this paper is to analyse the liaison phenomenon in a no-spontaneous task. The target audience is Greek-Cypriot learners in the French studies program of the University of Cyprus. Two different groups, 7 in 1st year of studies and 17 in 4th year of studies, have been recorded reading the same text. Our study is based on two hypotheses: 1. all students realising obligatory liaisons and, 2. the 4th year students realising the same liaisons as native speakers.
Keywords: consonant linking; French as foreign language; Greek-Cypriot speaking learners; learners in University context; intermediate/advanced learners